A Living Qur’an Study of the Philanthropic Programs of Dompet Dhuafa Waspada North Sumatra - Ade Mahri Kurniawan Rambe; Mardhiah Abbas (Journal of Indonesian Islamic Studies, 2026)
This study examines the implementation of Qur’anic values in the philanthropic programs of Dompet Dhuafa Waspada North Sumatra through the perspective of Living Qur’an. This research uses a qualitative method with a Living Qur’an approach. Primary data were obtained through interviews with the head of Dompet Dhuafa Waspada North Sumatra, while secondary data were collected from documentation, official institutional publications, books, journal articles, and other academic sources. The data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings show that the educational, health, economic empowerment, and humanitarian programs implemented by Dompet Dhuafa Waspada North Sumatra represent the actualization of Qur’anic values in social life. Educational programs reflect the value of knowledge, health programs represent the protection of human life, economic empowerment programs encourage effort and independence, while humanitarian programs express social care and generosity. These findings indicate that Qur’anic values are not only understood normatively but are also practiced through philanthropic activities that provide direct benefits to society.